2003
DOI: 10.1538/expanim.52.153
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of Penile Reflexes and Copulatory Behavior in Male Rats.

Abstract: First, pubertal development of the penile reflexes, e.g., erections, cups and flips in Wistar-Imamichi male rats was investigated following sheath retraction. Second, the penile reflexes and copulatory behavior in the above males were compared between 10 and 44 weeks of age. The penile reflexes in Wistar-Imamichi rats began to appear from day 26, and all males displayed full components of the reflexes on day 47. The occurrence rates and mean numbers of erections, cups and flips in aged adults were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We have shown previously that these cells in the rat CC are arranged as a subendothelial layer, whereas in humans they are more homogeneously distributed in the trabeculae (Pinheiro et al, 2000). Furthermore, in the aged rat, when there is already a loss of sexual function (Saito et al, 2003), this smooth muscle layer is markedly thicker and the sinusoidal vascular space is diminished (Machado et al, 2008). Thus, the radiation-induced, transient increase in smooth muscle should likewise lead to a reduction in the lumen of the cavernosal sinusoids.…”
Section: <0001mentioning
confidence: 92%
“…We have shown previously that these cells in the rat CC are arranged as a subendothelial layer, whereas in humans they are more homogeneously distributed in the trabeculae (Pinheiro et al, 2000). Furthermore, in the aged rat, when there is already a loss of sexual function (Saito et al, 2003), this smooth muscle layer is markedly thicker and the sinusoidal vascular space is diminished (Machado et al, 2008). Thus, the radiation-induced, transient increase in smooth muscle should likewise lead to a reduction in the lumen of the cavernosal sinusoids.…”
Section: <0001mentioning
confidence: 92%
“…Saito et al [25,27] demonstrated that penile reflexes and copulatory behavior in 44-week-old male rats are decreased as compared with 10-week-old male rats. Cardiovascular sudden death of elderly men during sexual activity has been reported [19,23,29] and is considered to be a serious problem.…”
mentioning
confidence: 99%
“…The aim of the present study was to investigate how ageing influences HR during copulatory behavior in males using a rat model. Experimental animals: On the basis of previous studies and observations [25,27], we used in our experiments specific-pathogen-free male Wistar-Imamichi rats that were 48 weeks old (aged, n=4) and 10 weeks old (young, n=6), and 10-week-old female rats (raised in our laboratory). All animals were acclimatized in an animal room (12-h light/dark cycle and a temperature of 23-25°C) and were given free access to water and food.…”
mentioning
confidence: 99%